CATALYTIC ACTIVITY CoMo/USY ON DEOXYGENATION REACTION OF 4-METHOXYPHENOL IN BATCH REACTOR - Khoirina Dwi Nugrahaningtyas; Irma Fadhila Putri; Eddy Heraldy (UNIVERSITAS SEBELAS MARET (UNS), 2017)
This research was conducted to study the effect of catalyst type of CoMo/USY and the reaction time on the deoxygenation reaction of 4-methoxyphenol. The catalyst type used were CoMo/USY, Co-Mo/USY, and Mo-Co/USY. The product was analyzed by gas chromatography (GC) and gas chromatography-mass spectrometry (GC-MS). The activity of the Co-Mo/USY catalyst is higher than CoMo/USY and Mo-Co/USY, it can be seen from the value of total yield and the selectivity. The Co-Mo/USY catalysts shows a significant increasing on the total yield percentage (from 3.71 % to 9.41 %) during catalytic testing. The Co-Mo/USY catalyst has a highest selectivity toward 1,4-dimethoxybenzene product when the reaction time was one hour (0.92 %) and selectivity toward 1,4-dihidroxybenzene when reaction time two hours (0.43 %).